Modularized device and process for electrochemical lithium element recovery in combination with flow battery
By using a highly catalytically active single-atom nickel carbon felt electrode and redox electricity pair conversion reaction in zinc-iodine batteries, combined with the electrode electrolyte interface reaction of the liquid flow battery device, the problem of the loss of active substances and the increase in the irreversibility of electrode reactions in the low temperature environment of lithium batteries is solved, and efficient lithium element recovery and extraction efficiency is achieved.
Patent Information
- Application Number
- CN202411895750.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-18
AI Technical Summary
The existing zinc-iodine batteries have problems such as loss of active substances, damage to the internal structure of the battery and increasing irreversibility of electrode reactions during charging and discharging under normal temperature and low temperature environments, which limits their normal operation and large-scale development under low temperature conditions.
The high catalytically active single-atom nickel carbon felt electrode and redox electricity pair conversion reaction is adopted, and the reaction is carried out at the electrode electrolyte interface through the liquid flow battery device to promote the leaching of lithium ions in waste lithium iron phosphate, and is collected at the negative electrode through the cationic membrane to achieve the recovery of lithium elements.
The efficient recycling of lithium elements in waste lithium iron phosphate is achieved, and the lithium ion leaching rate can reach 90%. Under the 0-5V voltage window and 25mA/cm2 current density, the 6-hour lithium extraction efficiency reaches 74%, while reducing costs and environmental pollution.
Smart Images

Figure CN119650738A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemical lithium recovery, and specifically relates to redox couple electrolyte design and electrode material modification and selection. Background Art
[0002] At present, the scale of my country's lithium battery market is still expanding rapidly, and the market is about to usher in a large-scale "retirement wave" of power batteries. In 2022, the retirement volume of lithium-ion batteries used for power batteries in my country will be 274,000 tons. It is predicted that by 2025, the cumulative retirement volume of power batteries in my country will reach 960,000 tons. According to calculations, the actual market size of power battery recycling in my country in 2022 will be about 14.6 billion yuan, and it is expected to reach 140.6 billion yuan by 2030. With the rapid development of the domestic electric vehicle industry, the consumption of lithium iron phosphate (LFP) batteries has exploded. The first batch of lithium batteries is about to reach the end of their service life. The cascade utilization of old batteries, the proper treatment of hazardous waste from waste batteries, and the effective recycling of useful materials are becoming increasingly urgent.
[0003] Compared with other methods such as mechanical separation and wet leaching, electrochemical recovery has the advantages of high purification rate, high accuracy and low pollution. It is very necessary to improve the electrochemical reaction kinetics by modifying the solid-liquid interface of the electrode electrolyte to improve the current electrochemical recovery of waste lithium iron phosphate.
[0004] The positive electrode material of zinc-iodine batteries directly determines their energy density, power density and electrochemical stability. Problems such as the dissolution of iodine intermediates and the corrosion of zinc anodes are particularly prominent. These problems lead to the loss of active substances during the battery's charging and discharging process at room temperature and low temperature, the destruction of the battery's internal structure, and the increase in the irreversibility of the electrode reaction. The large capacity attenuation at low temperatures has further limited the large-scale development of aqueous zinc-iodine batteries, making them unable to operate normally under low temperature conditions and unable to fully meet the strict requirements of large-scale energy storage systems for high-performance batteries. Summary of the invention
[0005] The purpose of the present invention is to combine the structure of a liquid flow battery device and utilize the electrode electrolyte interface reaction to increase the leaching rate of lithium ions, and to provide a method and device for electrochemically extracting lithium elements from waste lithium iron phosphate.
[0006] To achieve the object of the present invention, the method and device described in the present invention utilizes highly catalytically active single-atom nickel carbon felt to catalyze [Fe(CN)6] 4- / [Fe(CN)6] 3— The rapid redox reaction promotes the leaching of lithium ions in waste lithium iron phosphate. At the same time, under the action of the electric field, they are collected at the negative electrode through the cationic membrane, and the lithium ions in the waste lithium iron phosphate electrode are recovered to obtain by-products.
[0007] The present invention provides the following steps for preparing the positive electrode single-atom nickel-carbon felt electrode:
[0008] (1) Commercial carbon felt was pretreated with concentrated nitric acid at 90°C for 10 h to remove surface impurities and increase hydrophilicity to form ordinary single-atom-loaded carbon felt, which was then dried in an oven.
[0009] (2) The pretreated carbon felt is immersed in a 0.05 mol / L nickel nitrate solution for 12 h, dried in an oven, and annealed at 800° C. in a tube furnace in a 95% argon and 5% hydrogen mixed gas to reduce the nickel nitrate to nickel element.
[0010] (3) Soaking in concentrated hydrochloric acid for 4 h to remove excess nickel and form single-atom nickel clusters, ultrasonically treating with deionized water for 10 min, and washing three times to obtain single-atom nickel-loaded carbon felt.
[0011] The synthesis process of negative electrode carbon felt is as follows;
[0012] (4) Commercial carbon felt is pretreated with concentrated nitric acid at 90°C for 10 h to remove surface impurities and increase hydrophilicity to form electrode carbon felt, which is then dried in an oven.
[0013] (5) Size 1*1cm 2 A platinum electrode is placed in the center of the electrode carbon felt as the negative electrode.
[0014] Wherein, the concentration of concentrated nitric acid in steps (1) and (4) is 68%.
[0015] Preferably, the immersion in the nickel nitrate solution with a concentration of 0.05 mol / L in step (2) is: 0.9 g nickel nitrate is dissolved in 100 ml water.
[0016] Preferably, the calcination in step (2) is high temperature annealing at 800° C. for 2 h in a tubular furnace in an atmosphere of 95% argon and 5% hydrogen.
[0017] Preferably, the nickel nitrate solution is heated for 6 h, 10 h or 14 h.
[0018] Preferably, the tubular furnace annealing time is 2 h, 4 h, or 6 h.
[0019] The positive and negative carbon felt electrode materials in any of the above steps (3) and (5) are used as positive and negative electrode materials in a liquid flow battery device.
[0020] In the above application, the operation of the flow battery lithium ion recovery device using positive and negative carbon felt electrode materials as electrode materials includes the following steps:
[0021] (6) Lithium ion leaching: Mix the waste lithium iron phosphate powder with 100 mL of 0.05 mol / L potassium ferrocyanide solution and add it to the positive electrode tank. Stir and react for 2 h to use [Fe(CN)6] 3- The oxidizing property of Fe in lithium iron phosphate 2+ Oxidized to Fe 3+ , forming FePO4 byproduct in the cathode tank, the specific process is as shown in formula (1):
[0022] [Fe(CN)6] 3- +LiFePO4=Li + +[Fe(CN)6] 4- +FePO4 (1)
[0023] (7) Lithium ion diffusion recovery: The positive and negative electrodes and the naphthol 115 cationic diaphragm are sequentially loaded into the battery cell to form a liquid flow battery device, which is then connected to a Coster electrochemical workstation with a voltage range of 0-5 V and a current density of 25 mA / cm 2 The electrolysis time is 6 hours. The negative electrode tank generates hydrogen by electrolysis as shown in formula (2), producing LiOH. The liquid in the negative electrode tank is taken out and the lithium content is tested by inductively coupled plasma (ICP). The liquid is dried to obtain pure lithium salt.
[0024] 2H2O+2e - =2OH - +H2↑ (2)
[0025] (8) The recovered device converts [Fe(CN)6] 4- Reduction to [Fe(CN)6] 3- , realizing the recycling of redox couples.
[0026] The beneficial effects of the present invention are:
[0027] 1. The present invention designs a liquid flow battery device based on a highly catalytically active single-atom nickel electrode and a redox couple valence-changing reaction to realize the recovery of lithium elements in waste lithium iron phosphate. It has the following advantages: the synthesis method of the single-atom nickel carbon felt electrode material is simple, and the electrochemical recovery method can obtain purer lithium salts and by-products compared with the pyrometallurgical method and the wet method, which has low cost, low production difficulty, and is environmentally friendly; secondly, the electrolyte is an aqueous solution, which is non-toxic, highly safe, low-priced, and does not produce pollution.
[0028] 2. The present invention combines the structure of a flow battery device with the electrode electrolyte interface reaction, and the lithium ion leaching rate can reach 90% in the voltage window of 0-5V and 25mA / cm 2 At a current density of , the lithium extraction efficiency can reach 74% in 6 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a microscopic scanning electron microscope (SEM) image of the single-atom nickel-carbon felt positive electrode after annealing and acid etching prepared in Example 1;
[0030] Figure 2 A photo of a physical device of the present invention;
[0031] Figure 3 This is a schematic diagram of the electrochemical lithium recovery device for a liquid flow battery of the present invention;
[0032] Figure 4 This is a microscopic scanning electron microscope (SEM) image of the nickel single-atom carbon felt positive electrode prepared in Example 1;
[0033] Figure 5 This is a microscopic scanning electron microscope (SEM) image of the carbon felt positive electrode prepared in the comparative example;
[0034] Figure 6 This is the X-ray diffraction (XRD) pattern of the powder test obtained after drying the liquid recovered from the negative electrode side liquid storage tank.
[0035] Figure 7 The ICP test results and corresponding extraction rates of Examples 1-5 and the comparative example are shown. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments:
[0037] Example 1
[0038] Step 1: The commercial carbon felt is pretreated with concentrated nitric acid at 90°C for 10 hours to remove surface impurities, increase hydrophilicity, and form a carbon felt that can load single atoms.
[0039] Step 2: Soak the pretreated carbon felt in a 0.05 mol / L nickel nitrate solution for 12 hours, dry it in an oven, and anneal it at 800°C for 2 hours in a tube furnace in a 95% argon 5% hydrogen mixed gas to reduce the nickel nitrate to nickel element.
[0040] Step 3: Soak the carbon felt obtained in the second step in concentrated hydrochloric acid for 4 hours to remove excess nickel and form single-atom nickel clusters. Ultrasonicate with deionized water for 10 minutes and wash three times to obtain single-atom nickel-loaded carbon felt. The microscopic morphology of the felt is shown in the scanning electron microscope (SEM) image. Figure 1 As shown. Figure 2 Size 1*1cm 2 A platinum sheet electrode is placed in the center of the carbon felt electrode as the negative electrode.
[0041] Step 4: Mix the waste lithium iron phosphate powder with 100mL of 0.05mol / L potassium ferrocyanide solution and add it to the positive electrode tank. Stir and react for 2h. Assemble the positive and negative electrodes obtained in the third step and the naphthol 115 cationic membrane at the cell to form a liquid flow battery device. Connect the device to the Coster electrochemical workstation with a voltage range of 0-5V and a current density of 25mA / cm 2 The electrolysis time is 6h. After the electrolysis process is completed, the SEM image is as follows: Figure 5 , the lithium extraction rate was 74%.
[0042] Example 2
[0043] Step 1: Pre-treat the commercial carbon felt with concentrated nitric acid at 90°C for 10 hours to remove surface impurities, increase hydrophilicity, and form a carbon felt that can load single atoms.
[0044] Step 2: Soak the pretreated carbon felt in a 0.05 mol / L nickel nitrate solution for 8 hours, dry it in an oven, and anneal it at 800°C for 2 hours in a tube furnace in a 95% argon 5% hydrogen mixed gas to reduce the nickel nitrate to nickel element.
[0045] Step 3: Soak the carbon felt obtained in the second step in concentrated hydrochloric acid for 4 hours to remove excess nickel and form single-atom nickel clusters. Ultrasonicate with deionized water for 10 minutes and wash three times to obtain single-atom nickel-loaded carbon felt. The microscopic morphology of the felt is shown in the scanning electron microscope (SEM) image. Figure 1 As shown. Figure 2 Size 1*1cm 2 The platinum electrode is placed in the center of the carbon felt electrode as the negative electrode.
[0046] Step 4: Mix the waste lithium iron phosphate powder with 100mL of 0.05mol / L potassium ferrocyanide solution and add it to the positive electrode tank. Stir and react for 2h. Assemble the positive and negative electrodes obtained in the third step and the naphthol 115 cationic membrane at the cell to form a liquid flow battery device. Connect the device to the Coster electrochemical workstation with a voltage range of 0-5V and a current density of 25mA / cm 2 The electrolysis time is 6h. After the electrolysis process is completed, the SEM image is as follows: Figure 5 , the lithium extraction rate was 50.8%.
[0047] Example 3
[0048] Step 1: The commercial carbon felt is pretreated with concentrated nitric acid at 90°C for 10 hours to remove surface impurities, increase hydrophilicity, and form a carbon felt that can load single atoms.
[0049] Step 2: Soak the pretreated carbon felt in a 0.05 mol / L nickel nitrate solution for 16 hours, dry it in an oven, and anneal it at 800°C for 2 hours in a tubular furnace in a 95% argon 5% hydrogen mixed gas to reduce the nickel nitrate to nickel element.
[0050] Step 3: Soak the carbon felt obtained in the second step in concentrated hydrochloric acid for 4 hours to remove excess nickel and form single-atom nickel clusters. Ultrasonicate with deionized water for 10 minutes and wash three times to obtain single-atom nickel-loaded carbon felt. The microscopic morphology of the felt is shown in the scanning electron microscope (SEM) image. Figure 1 As shown. Figure 2 Size 1*1cm 2 A platinum sheet electrode is placed in the center of the carbon felt electrode as the negative electrode.
[0051] Step 4: Mix the waste lithium iron phosphate powder with 100mL of 0.05mol / L potassium ferrocyanide solution and add it to the positive electrode tank. Stir and react for 2h. Assemble the positive and negative electrodes obtained in the third step and the naphthol 115 cationic membrane at the cell to form a liquid flow battery device. Connect the device to the Coster electrochemical workstation with a voltage range of 0-5V and a current density of 25mA / cm 2 The electrolysis time is 6h. After the electrolysis process is completed, the SEM image is as follows: Figure 5 , the lithium extraction rate was 31.2%.
[0052] Example 4
[0053] In the first step, the commercial carbon felt was pretreated with concentrated nitric acid at 90°C for 10 h to remove surface impurities, increase hydrophilicity, and form a carbon felt that can load single atoms.
[0054] Step 2: Soak the pretreated carbon felt in a 0.05 mol / L nickel nitrate solution for 8 hours, dry it in an oven, and anneal it at 800°C for 4 hours in a tube furnace in a 95% argon 5% hydrogen mixed gas to reduce the nickel nitrate to nickel element.
[0055] Step 3: Soak the carbon felt obtained in the second step in concentrated hydrochloric acid for 4 hours to remove excess nickel and form single-atom nickel clusters. Ultrasonicate with deionized water for 10 minutes and wash three times to obtain single-atom nickel-loaded carbon felt. The microscopic morphology of the felt is shown in the scanning electron microscope (SEM) image. Figure 1 As shown. Figure 2 Size 1*1cm 2 A platinum sheet electrode is placed in the center of the carbon felt electrode as the negative electrode.
[0056] Step 4: Mix the waste lithium iron phosphate powder with 100mL of 0.05mol / L potassium ferrocyanide solution and add it to the positive electrode tank. Stir and react for 2h. Assemble the positive and negative electrodes obtained in the third step and the naphthol 115 cationic membrane at the cell to form a liquid flow battery device. Connect the device to the Coster electrochemical workstation with a voltage range of 0-5V and a current density of 25mA / cm 2 The electrolysis time is 6h. After the electrolysis process is completed, the SEM image is as follows: Figure 5 , the lithium extraction rate was 10.2%.
[0057] Example 5
[0058] Step 1: The commercial carbon felt is pretreated with concentrated nitric acid at 90°C for 10 hours to remove surface impurities, increase hydrophilicity, and form a carbon felt that can load single atoms.
[0059] Step 2: Soak the pretreated carbon felt in a 0.05 mol / L nickel nitrate solution for 12 hours, dry it in an oven, and anneal it at 800°C for 6 hours in a tube furnace in a 95% argon 5% hydrogen mixed gas to reduce the nickel nitrate to nickel element.
[0060] Step 3: Soak the carbon felt obtained in step 2 in concentrated hydrochloric acid for 4 hours to remove excess nickel and form single-atom nickel clusters. Ultrasonicate with deionized water for 10 minutes and wash three times to obtain single-atom nickel-loaded carbon felt. The microscopic morphology of the felt is shown in the scanning electron microscope (SEM) image. Figure 1 As shown. Figure 2 Size 1*1cm 2 A platinum sheet electrode is placed in the center of the carbon felt electrode as the negative electrode.
[0061] Step 4: Mix the waste lithium iron phosphate powder with 100mL of 0.05mol / L potassium ferrocyanide solution and add it to the positive electrode tank. Stir and react for 2h. Assemble the positive and negative electrodes obtained in the third step and the naphthol 115 cationic membrane at the cell to form a liquid flow battery device. Connect the device to the Coster electrochemical workstation with a voltage range of 0-5V and a current density of 25mA / cm 2 The electrolysis time is 6h. After the electrolysis process is completed, the SEM image is as follows: Figure 5 , the lithium extraction rate is 12.5%.
[0062] Comparative Example
[0063] Step 1: The commercial carbon felt was pretreated with concentrated nitric acid at 90°C for 10 h to remove surface impurities and increase hydrophilicity, thereby forming a pretreated carbon felt electrode as the positive electrode.
[0064] The second step is, Figure 2 Size 1*1cm 2A platinum sheet electrode is placed in the center of the carbon felt electrode as the negative electrode.
[0065] Step 3: Mix the waste lithium iron phosphate powder with 100mL of 0.05mol / L potassium ferrocyanide solution and add it to the positive electrode tank. Stir and react for 2h. Assemble the positive and negative electrodes obtained in the third step and the naphthol 115 cationic membrane at the cell to form a liquid flow battery device. Connect the device to the Coster electrochemical workstation with a voltage range of 0-5V and a current density of 25mA / cm 2 The electrolysis time is 6h. After the electrolysis process is completed, the SEM image is as follows: Figure 6 , lithium extraction rate 28.5%.
[0066]
[0067] The cathode liquid in the negative electrode tank after electrolysis was measured by ICP test, and the extraction rate was calculated by calculating the lithium content in the cathode liquid using formula (3).
[0068] like Figure 1 As shown in the figure, the positive electrode single-atom nickel carbon felt electrode fiber after annealing and acid etching, and a relatively smooth and complete fiber structure was observed, which is conducive to improving the conductivity of the carbon felt. And the acid etching did not destroy the structure of the carbon felt fiber.
[0069] like Figure 2 As shown, a photo of the actual device of the present invention, the positive electrode side liquid storage tank is the waste lithium iron phosphate leaching side, which is a potassium ferrocyanide solution, the negative electrode side liquid storage tank is the lithium element collection side, which is a lithium chloride solution, the conductive carbon plate positive electrode at the battery cell is a highly catalytically active loaded single-atom nickel carbon felt, and the negative electrode is a platinum sheet electrode superimposed on carbon felt, the positive electrode side tank supplies liquid to the battery cell chamber through a peristaltic pump, and the negative electrode side tank supplies liquid to the recovery liquid chamber through a peristaltic pump.
[0070] like Figure 3 As shown in the schematic diagram of the device of the present invention, the positive electrode side liquid storage tank uses [Fe(CN)6] 4- / [Fe(CN)6] 3- The redox couple leaches the lithium ions in the waste lithium iron phosphate, and at the same time, the lithium ions are diffused from the positive electrode through the cation membrane to the negative electrode side storage tank through the action of the electric field. After drying, relatively pure LiOH and by-product FePO4 can be obtained.
[0071] like Figure 4 , 5As shown, the SEM comparison pictures of the carbon felt electrode loaded with single-atom nickel and the ordinary carbon felt electrode fiber after the electrochemical lithium extraction process of Example 1 and the comparative example, it can be clearly seen from the picture that after electrochemistry, the carbon felt electrode fiber loaded with single-atom nickel can still maintain a relatively intact fiber morphology, while the ordinary carbon felt electrode fiber shows obvious breakage phenomenon, and the resulting problems such as poor conductivity lead to a reduction in the efficiency of electrochemical lithium extraction.
[0072] like Figure 6 As shown, the XRD spectrum of the powder sample of the lithium salt obtained from the negative electrode side liquid storage tank of the device after drying shows that the comparison with the LiOH standard PDF card corresponds to the main diffraction peak.
[0073] like Figure 7 As shown, the treatment effect of the single-atom nickel carbon felt electrode in Example 1 is the best, and the extraction rate can reach 74%, which is higher than the 50.8% and 31.2% extraction rates of Examples 2 and 3 soaked in nickel nitrate for 8 hours and 16 hours, that is, the carbon felt electrode soaked for 12 hours has the best effect; it is higher than the 10.2% and 12.5% extraction rates of Examples 4 and 5 annealed for 4 hours and 6 hours, that is, the carbon felt electrode annealed for 2 hours has the best effect; compared with the comparison example of the carbon felt electrode without single-atom nickel loading, the extraction rate of 28.5% has been greatly improved.
Claims
1. A modular device for electrochemical lithium recovery in combination with a flow battery, characterized in that The liquid storage tank on the positive electrode side is the leaching side of waste lithium iron phosphate, which is a potassium ferrocyanide solution. The liquid storage tank on the negative electrode side is the lithium element collection side, which is a lithium chloride solution. The positive electrode of the conductive carbon plate at the battery cell is a highly catalytically active loaded single-atom nickel carbon felt, and the negative electrode is a platinum sheet electrode superimposed on carbon felt.
2. The modular device according to claim 1, characterized in that The modular device also includes a positive electrode side tank and a negative electrode side tank. The positive electrode side tank supplies liquid to the battery cell chamber through a peristaltic pump, and the negative electrode side tank supplies liquid to the recovery liquid chamber through a peristaltic pump.
3. The synthesis process of positive electrode carbon felt is as follows: (1) The commercial carbon felt was immersed in concentrated nitric acid at 90°C for 10 h to remove surface impurities and increase hydrophilicity, thereby forming a common single-atom-loaded carbon felt. (2) The pretreated carbon felt is immersed in a 0.05 mol / L nickel nitrate solution for 12 h, dried in an oven, and annealed at 800° C. in a tube furnace in a 95% argon and 5% hydrogen mixed gas to reduce the nickel nitrate to nickel element. (3) Soaking in concentrated hydrochloric acid for 4 h to remove excess nickel, ultrasonicating with deionized water for 10 min, and washing three times to obtain single-atom nickel-carbon felt.
4. The synthesis process of negative electrode carbon felt is as follows: (1) The commercial carbon felt was immersed in concentrated nitric acid at 90° C. for 10 h to remove surface impurities and increase hydrophilicity, thereby forming a treated carbon felt. (2) Size 1*1cm 2 A platinum electrode is placed in the center of the electrode carbon felt as the negative electrode.
5. The single-atom nickel material according to claim 2, characterized in that: In step (2), the concentration of nickel nitrate is 0.05 mol / L.
6. The single-atom nickel material according to claim 2, characterized in that: In step (2), the heating condition of the tubular furnace is: heating at 800° C. for 2 h.
7. The positive electrode tank electrolyte according to claim 1, characterized in that: The concentration of the potassium ferrocyanide is 0.05 mol / L: 15.47 g of potassium ferrocyanide is dissolved in 1000 ml of water.
8. The negative electrode tank electrolyte according to claim 1, characterized in that: The concentration of the lithium chloride is 0.05 mol / L: 2.12 g of lithium chloride is dissolved in 1000 ml of water.
9. The liquid flow device according to claim 1, characterized in that: The electrolysis voltage range is 0-5V and the current density is 25mA / cm 2 , the electrolysis time is 6h.